WANGI: Inovasi Detergen Ramah Lingkungan Berbahan Dasar Daun Waru (Hibiscus Tiliaceus) dengan Tambahan Daun Kemangi (Ocimum Sanctum) Sebagai Upaya Kuratif Permasalahan Air Sungai Di Indonesia - Muhammad Avreel Arya Pratama; Mirza Muhammad Mumtaza Mirza Muhammad Mumtaza (Jurnal Integrasi Sains dan Quran, 2025)
River pollution occurs when there are materials that enter the river causing the quality of river water to decrease so that it does not meet quality standards and cannot be used for various purposes, such as drinking and bathing. One of the causes of river pollution is household waste in the form of detergent water. Commercial detergents that are often used contain active ingredients Alkyl Benzene Sulfonates (ABS) and Linear Alkyl Sulfonate (LAS) which have a negative impact on living things and the environment. One of the efforts related to this problem is to make an environmentally friendly detergent made from waru leaves with the addition of essential oil of basil leaves. The type of research used is descriptive with a qualitative approach. Data collection was carried out by observation, experimentation, and literature study. Indicators of product effectiveness include: 1) pH test; 2) organoleptic test; 3) water insoluble material test; 4) foam height test. From the research that has been done, the results obtained in the product pH test meet SNI standards with a pH of 6 so the product is safe for the skin. In the organoleptic test the product has a distinctive aroma of basil with a thick texture. The water insoluble material test meets SNI standards with no sediment in the product. The foam height test shows the product has a foam height of 66 mm.